A new method to analyze distortion product otoacoustic emissions (DPOAEs) in the high-frequency range up to 18 kHz using windowed periodograms - Hecker, Dietmar J.; Lohscheller, Joerg; Bader, Carl-Albert; Delb, Wolfgang; Schick, Bernhard; Dlugaiczyk, Julia (IEEE transactions on biomedical engineering, 2011)
Distortion product otoacoustic emissions (DPOAEs) are widely used as an objective examination procedure to determine cochlear function. In a clinical routine setting, the amplitude of the DPOAE signal at 2f1-f2 is applied as an indicator for a potential hearing loss up to 8 kHz. Due to their poor signal-to-noise ratio, meatal nodes from standing waves and calibration issues, high-frequency DPOAEs >; 8 kHz have hardly been addressed in experimental and clinical audiology so far. Here, we present a new method of measuring DPOAE signal levels based on optimal maximum likelihood estimation with windowed power spectral density estimation of stochastic signals and filtering theory. Analysis of simulated data showed that the proposed method effectively reduces the disturbing noise floor compared to conventional averaging techniques. Robust DPOAE signals were measured in 20 ears from ten normally hearing young adults (21-27 years) from 0.5 to 18 kHz . Repeated DPOAE recordings in one individual yielded a good to very good test-retest reliability of the proposed method. These observations are discussed in the context of DPOAE signal processing and possible clinical applications of high-frequency DPOAE measurements.